2016
DOI: 10.1016/j.ejca.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for secondary malignancy in patients with neuroblastoma after treatment with 131I-metaiodobenzylguanidine

Abstract: Several reports of second malignant neoplasm (SMN) in patients with relapsed neuroblastoma after treatment with (131)I-MIBG suggest the possibility of increased risk. Incidence of and risk factors for SMN after (131)I-MIBG have not been defined. This is a multi-institutional retrospective review of patients with neuroblastoma treated with (131)I-MIBG therapy. A competing risk approach was used to calculate the cumulative incidence of SMN from time of first exposure to (131)I-MIBG. A competing risk regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…Analyses of 9,432 long-term neuroblastoma survivors in 3 major studies indicated that 96 patients developed second cancers, including carcinomas, soft tissue sarcomas, glioblastomas, meningioma, melanomas, and hematologic malignancies, but none developed medulloblastoma (Table 3). [5][6][7] Neuroblastoma and, less commonly, medulloblastoma, have been reported in patients with cancer predisposition syn- [22][23][24] Our patient did not have clinical stigmata of these conditions and her genetic testing was negative for these syndromes.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Analyses of 9,432 long-term neuroblastoma survivors in 3 major studies indicated that 96 patients developed second cancers, including carcinomas, soft tissue sarcomas, glioblastomas, meningioma, melanomas, and hematologic malignancies, but none developed medulloblastoma (Table 3). [5][6][7] Neuroblastoma and, less commonly, medulloblastoma, have been reported in patients with cancer predisposition syn- [22][23][24] Our patient did not have clinical stigmata of these conditions and her genetic testing was negative for these syndromes.…”
Section: Discussionmentioning
confidence: 65%
“…Agda Karina Eterovic, PhD a ; Ossama M. Maher, MD b ; Joya Chandra, PhD c ; Ken Chen, PhD d ; Jason Huse, MD, PhD e ; and Wafik Zaky, MD c cers have mostly occurred many years after long-term surveillance. [5][6][7] This report presents a case of medulloblastoma in a child 5 months after successful treatment of stage IV neuroblastoma, and discusses the findings in the DNA sequencing results of both the resected posterior fossa tumor and the germline mutations.…”
Section: Metachronous Medulloblastoma In a Child With Successfully Trmentioning
confidence: 98%
“…Other commonly observed toxicities are transient thyroid dysfunction, sialoadenitis (100), hepatic transaminitis (101), and mild acute hypertension (102). The incidence of secondary malignancy is similar to that observed in children treated with chemotherapy with a cumulative incidence of 7.6% and 14.3% at 5 and 10 y after therapy, respectively (103). Secondary malignancies including acute nonlymphoblastic leukemia, chronic myelomonocytic leukemia, angiomatoid malignant fibrous histiocytoma, malignant schwannoma, and rhabdomyosarcoma have been reported to occur at a median of 3 y (1-15 y) (104).…”
Section: Net Targeting For Therapy 123 I/ 131 I-mibg Theranostics Formentioning
confidence: 81%
“…It ranges from an adrenal mass tumor that regresses without treatment to a metastatic tumor that causes critical illness [ 6 ]. At present, while intensive therapies can be beneficial for patients with localized disease, these therapies have frequently not been useful against patients with high-risk disease (approximately 40% of cases associated with the extent of metastases and genetic factors) nor patients with relapse [ 7 , 8 ]. Hence, novel therapies based on immunotherapy were subsequently developed to improve survival for high-risk patients.…”
Section: Introductionmentioning
confidence: 99%